Clustering the Spread of ISPA Disease Using the Fuzzy C-Means Algorithm in Aceh Utara - Rozzi Kesuma Dinata; Bustami Bustami; Sujacka Retno; Azrai Putra Barumun Daulay (Geviva Edukasi Trans Teknologi, 2022)
ISPA disease is one of the most common types of disease suffered in Aceh. The method used in this research is fuzzy c means algorithm to cluster the spread of ISPA disease areas in Aceh Utara. The data used is the data on patients with ISPA in 2021 obtained from Cut Meutia General Hospital and Arun Hospital. The attributes used consist of the patient's age, patient's address, patient's gender and the type of ISPA the patient suffered. In this research only focused on 3 types of ISPA, namely Pneumonia, Bronchitis and ISPA. The existing data will then be grouped into 3 clusters, namely low cluster, medium cluster and high cluster. The results of clustering the spread of ISPA in Aceh Utara show that the highest case is in Dewantara District, the medium cluster are Muara Batu, Nisam, Nisam Antara, Sawang, and Tanah Jambo Aye Districts, and the low cluster is Baktiya, Baktiya Barat, Banda Baro, Cot Girek, Geureudong Pase, Kuta Makmur, Langkahan, Lapang, Lhoksukon, Matang Kuli, Meurah Mulia, Nibong, Paya Bakong, Pirak Timu, Samudera, Seunudon, Simpang Keramat, Syamtalira Aron, Syamtalira Bayu, Tanah Luas and Tanah Pasir Districts. With the results of this clustering, it is expected that the provision of drug stocks for ISPA will be prioritized in cluster areas with the highest spread rates.